Interfaces Between Graphene‐Related Materials and MAPbI3: Insights from First‐Principles. Issue 22 (7th August 2018) - Volonakis, George; Giustino, Feliciano
Abstract: Given the unique and complementary properties of halide perovskites and graphene, it has been a natural step to explore their combination for novel high‐performance solar cells. Within this research news the latest theoretical and computational works on interfaces between the prototype perovskite absorber methylammonium lead triiodide (CH3 NH3 PbI3 ) and graphene related materials (GRMs) are reviewed. In particular, recent works based on quantum‐mechanical calculations from first‐principles that probe the structural and electronic properties of interfaces between CH3 NH3 PbI3, pristine graphene, graphene‐oxide, and reduced graphene‐oxide are reviewed. How these studies investigate the fundamental mechanisms by which GRMs can improve perovskite based photovoltaics, and how these relate to the several available experimental studies that have clearly shown the positive effects of GRMs on both the charge extraction rates, and the stability of perovskite solar cells are discussed. Finally, the main challenges that remain to be addressed in order to model more realistic systems and further unravel the atomic‐scale details that underlie the properties of GRM/perovskite interfaces are discussed. Abstract : In this research news the latest theoretical and computational work on prototype interfaces between the perovskite absorber methylammonium lead triiodide (CH3 NH3 PbI3 ) and graphene related materials is summarized. The examples of pristine graphene, reduced graphene oxide, and graphene oxide in combination with CH3 NH3 PbI3 are considered, and the effects of their interactions on the structural and electronic properties of their interfaces are discussed in detail.